ASSESSMENT OF RADIATION RISK FROM DRINKING WATER AT PUBLIC FOUNTAINS ON THE WIDER TERRITORY OF KRUŠEVAC - Vučković, Biljana; Todorović, Nataša; Nikolov, Jovana; Radovanović, Dragan; Kevkić, Tijana (Bulletin of Natural Sciences Research, 2019)
Measurements of radon concentrations in drinking waters conducted on wider territory of the town of Kruševac included 16 public fountains, of which 4 are in the city itself and 12 in the surrounding area. Measurements of radon concentrations in water were carried out using radon detector RAD7 (DURRIDGE Co.). The values ​​of radon concentrations in water are in the range of (5.3 ± 0.8) Bq l-1 to (71.0 ± 7.2) Bq l-1 and are below the reference level of 100 Bq l-1, recommended by the European Commission. Since radon represents one of the most important causes of malignant diseases, annual effective doses of ingestion and inhalation are determined, whose mean values ​​are in the range of 0.04 mSv y-1 to 0.52 mSv y-1, and from 14.84 μSv y-1 to 198.8 μSv y-1, respectively. During sampling, water temperatures and their pH values were measured. These results are the first results of measuring radon in water in this area by this method. The aim of this paper is to evaluate whether there is, or not, a radiological risk to people's health due to the use of water primarily for drinking, but also for other purposes.
Keywords: Radon; Water; RAD7; Temperature; pH; Annual effective doses of internal radiation